Purification of sialoglycoproteins from bovine milk using serotonin-functionalized magnetic particles and their application against influenza A virus. Issue 8 (21st July 2020) - Wang, Xilong; Ma, Tianran; Yu, Hanjie; Chen, Zhuo; Zhu, Bojing; Chen, Wentian; Sun, Shisheng; Li, Zheng
Abstract : Serotonin-functionalized particles were used to isolate sialoglycoproteins, which have the ability to inhibit the attachment of IAV mimics to MDCK cells. Abstract : Sialylation is involved in receptor–ligand interactions, communication between cells, and host–pathogen interactions and it is involved in the ability of glycoproteins of bovine milk to inhibit the influenza A virus (IAV). The present paper describes a simple and efficient method to isolate sialoglycoproteins from bovine milk using serotonin-magnetic particle conjugates. Then, the isolated glycoproteins were analysed by lectin blotting and LC-MS/MS. The N -glycans on isolated glycoproteins were characterized by MALDI-TOF/TOF-MS. The role of the isolated sialoglycoproteins against IAV was validated in vitro . As a result, there were 91 proteins and 17 sialylated N -glycans to be identified. The isolated proteins have ability to inhibit attachment of IAV mimics to MDCK cells. However, the role of inhibition was abolished when the sialic acid moieties were destroyed. This method could provide useful information for the large-scale production of sialoglycoproteins from bovine milk against IAV.